220k views
9 votes
Simplify.
(–5q^2p)^3

User Hagakurje
by
5.6k points

2 Answers

4 votes

Answer:

-125q^6p^3

Explanation:

put -5 in () which equals (-5) then put a 1 on top of -5 and the 3 x 1 =3 so (-5)^3 then 2x3=6 so (-5)^3q^6 then 1x3=3 so (-5)^3q^6p^3 then do (-5)^3 which equals -125 then put q^6p^3 at the end which equals -125q^6p^3

User Jitendra Kulkarni
by
5.6k points
5 votes

Answer:

Explanation:


(a*b)^(n) = a^(n)*b^(n)\\\\(a^(n))^(m) = a^(m*n)\\\\ (-5q^(2)*p)^(3)= (-5)^(3)*q^(2*3)*p^(3)\\\\= -125q^(6)p^(3)

User Jamona Mican
by
5.5k points